1996
DOI: 10.1074/jbc.271.18.10697
|View full text |Cite
|
Sign up to set email alerts
|

AdipoQ Is a Novel Adipose-specific Gene Dysregulated in Obesity

Abstract: Adipose differentiation is accompanied by changes in cellular morphology, a dramatic accumulation of intracellular lipid and activation of a specific program of gene expression. Using an mRNA differential display technique, we have isolated a novel adipose cDNA, termed adipoQ. The adipoQ cDNA encodes a polypeptide of 247 amino acids with a secretory signal sequence at the amino terminus, a collagenous region (Gly-X-Y repeats), and a globular domain. The globular domain of adipoQ shares significant homology wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

50
1,400
3
74

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 2,011 publications
(1,527 citation statements)
references
References 69 publications
50
1,400
3
74
Order By: Relevance
“…The best‐characterized effects of adiponectin include enhanced insulin sensitivity, anti‐inflammatory properties, and inhibition of the development of atherosclerosis 38. In contrast to leptin, it has been shown that an increase in the fat mass decreases the circulating adiponectin level, whereas weight loss increases the adiponectin concentrations in obese human, primates, and rodents 39, 40. Similarly, adiponectin might be inversely related to adiposity in obese dogs,41 although there is a controversy about the inverse relationship 30, 42.…”
Section: Discussionmentioning
confidence: 99%
“…The best‐characterized effects of adiponectin include enhanced insulin sensitivity, anti‐inflammatory properties, and inhibition of the development of atherosclerosis 38. In contrast to leptin, it has been shown that an increase in the fat mass decreases the circulating adiponectin level, whereas weight loss increases the adiponectin concentrations in obese human, primates, and rodents 39, 40. Similarly, adiponectin might be inversely related to adiposity in obese dogs,41 although there is a controversy about the inverse relationship 30, 42.…”
Section: Discussionmentioning
confidence: 99%
“…Adiponectin was independently characterized in 1995 and 1996 by four groups using different methods, hence its alternative names of apM1 (adipose most abundant gene transcript 1), Acrp30 (adipocyte complement-related protein of 30 kDa), adipoQ, and GBP28 (gelatin binding protein of 28 kDa) (43)(44)(45)(46). Adiponectin is highly and specifically expressed in differentiated adipocytes and circulates at high levels in the bloodstream (47).…”
Section: Adiponectinmentioning
confidence: 99%
“…Adiponectin is an approximately 30-kDa polypeptide containing an Nterminal signal sequence, a variable domain, a collagen-like domain, and a C-terminal globular domain (43)(44)(45)(46). It shares strong sequence homology with type VIII and X collagen and complement component C1q (43)(44)(45)(46). Interestingly, the tertiary structure of the globular domain bears a striking similarity to TNF␣, despite a lack of homology in primary sequence (47).…”
Section: Adiponectinmentioning
confidence: 99%
“…One such molecule of great current interest is adiponectin, which is only secreted by the adipose cells [8][9][10]. Thiazolidinediones not only increase the concentration of total circulating adiponectin but also alter the relative abundance of the different molecular weight complexes [11].…”
Section: Introductionmentioning
confidence: 99%